2017
DOI: 10.4103/ijo.ijo_619_16
|View full text |Cite
|
Sign up to set email alerts
|

To assess knowledge and attitude of parents toward children suffering from strabismus in Indian subcontinent

Abstract: Purpose:Strabismus and anisometropia are the most common causes of amblyopia. It can be easily prevented or treated if detected early. With the changing socio-cultural-economic milieu of the society, the perspectives of strabismus in society are gradually changing but still adequate knowledge, awareness, and attitude of parents toward strabismus will help in preventing amblyopia and aid in the proper psychosocial adaptation of such children. This study aimed to assess knowledge and attitude of parents toward c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
31
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 25 publications
5
31
2
Order By: Relevance
“…is may be due to the difference in the study population who were agrarian and rural dwellers, which made them less aware of strabismus. However, this finding was lower than a study conducted in Jeddah (60-79%), India (94.7%), and Saudi (66.7%) [21,22,27]. is is due to the difference in the study setting since these studies were hospital-based.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…is may be due to the difference in the study population who were agrarian and rural dwellers, which made them less aware of strabismus. However, this finding was lower than a study conducted in Jeddah (60-79%), India (94.7%), and Saudi (66.7%) [21,22,27]. is is due to the difference in the study setting since these studies were hospital-based.…”
Section: Discussioncontrasting
confidence: 61%
“…Studies conducted in different regions of the world showed that there is a knowledge gap about strabismus. In India, 94.7% of participants had knew the consequence of strabismus [21], in Jeddah, 75% of participants knew etiologies [22], in Nigeria, 50% of participants did not know strabismus [23], and in Ethiopia, only 37.2% knew the cause of strabismus [9]. ere were studies conducted on the prevalence and psychological effects of strabismus.…”
Section: Introductionmentioning
confidence: 99%
“…This might eventually lead to multiple negative effects on the quality of life of the parents. [17] Regarding strabismus treatment dimension in the present study, participants' perceptions were modestly directed towards wearing glasses and surgical approaches rather than eye muscle exercise. Surgical treatment (24.8%) and medical therapy (20.2%) were reported as the prevalent perceived treatment options in another study.…”
Section: Discussionmentioning
confidence: 63%
“…This was typically consistent with another study in India where both relatives and the internet were the reliable sources of knowledge although Section: Ophthalmology most of the participating parents (60%) had low educational levels. [17] An early study in London has shown that the verbal information provided by the ophthalmologists had a superior role in providing adequate knowledge to the parents rather than those acquired from family support discussions and the internet. [29] However, the substantial increase in internet usage along with the expanding role of social media might represent a vital source of information.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation